THE EFFECT OF DRAW LABEL CAPTION STRATEGY ON STUDENTS’ WRITING DESCRIPTIVE TEXT ABILITY AT THE EIGHTH GRADE OF SMP NEGERI 7 PADANGSIDIMPUAN in 2020/2021 ACADEMIC YEAR - Zainab Harahap (JURNAL LINER (Language Intelligence and Educational Research), 2021)
Harahap, Zainab. 2020. The Effect of Draw Label Caption Strategy on Students’ Writing Descriptive Text Ability at The Eighth Grade of SMP Negeri 7 Padangsidimpuan in 2020/2021 Academic Year. Skripsi. Program Studi Pendidikan Bahasa Inggris. Institut Pendidikan Tapanuli Selatan. The purpose of this research are to find out: 1) the extent of the application of draw label caption strategy in teaching writing descriptive text ability at the eighth grade students of SMP Negeri 7 Padangsidimpuan. 2) the extent of the students’ writing descriptive text ability before and after using draw label caption strategy at the eighth grade of SMP Negeri 7 Padangsidimpuan, 3) whether there is any significant effect of draw label caption strategy on students’ writing descriptive text ability at the eighth grade of SMP Negeri 7 Padangsidimpuan. The population of this research all of the eighth grade students of SMP Negeri 7 Padangsidimpuan consists of 114 students. The sample is 26 students which are taken by purposive sampling. The research method is used by experimental method. Then, the data collected by using the observation sheet and test. The instrument used is a composition writing test. The average score of the application of draw label caption strategy is 3,2 categorized “ very good”. The calculation of t-test formula is higher than the score of t-table. The score of t-test is 3,49 meanwhile the score of t-table is 2,06 at 5 % significant level with (df) 24. And the hypothesis is accepted. It means that there is a significant effect of draw label caption strategy on students’ writing descriptive text ability at the eighth grade of SMP Negeri 7 Padangsidimpuan in 2020/2021 academic year. Keyword: Draw Label Caption Strategy, Writing Descriptive Text